Insufficient healthcare facilities in rural areas of Pakistan - Muhammad Sabir; Arsalan Khan; Abdul Majid (Journal of the Pakistan Medical Association, 2026)
Dear Editor We express our concern regarding the insufficient healthcare facilities in rural Pakistan. Primary healthcare is a fundamental human right vital for overall well-being. Despite international recognition of this right, urban areas in Pakistan receive the majority of resources, leaving rural regions underserved, despite comprising 62% of the population (1). The Community Health Index shows urban districts at 7.78 compared to 17.54 in rural areas, with an overall inequality ratio of 16.59, indicating disparities in health outcomes (2). Government public health spending remains at just 3% of GDP, far below the WHO’s recommended 6%, resulting in neglected infrastructure and limited access to advanced care (3) Rural populations depend on Basic Health Units (BHUs) and Rural Health Centres (RHCs), which are often underfunded and lack essential medicines, equipment, and qualified staff. (3). With only 1.09 doctors and 0.59 nurses or midwives per 1,000 people nationwide, these areas face acute workforce shortages, worsened by the migration of skilled professionals to cities (3). Poverty, rapid population growth, and low education levels further undermine health literacy and delay care-seeking. Additionally, stigma surrounding HIV, tuberculosis, and mental illness discourage timely treatment. Despite NGO efforts and public-private partnerships, rural healthcare remains critically inadequate (4). Improving accessibility, quality, and effectiveness of healthcare in rural Pakistan requires urgent attention. Strategies include ensuring the availability of qualified staff and medicines, increasing allowances for healthcare professionals, and developing well-equipped infrastructure. Comprehensive efforts should involve the allocation of financial resources to rural areas, deployment of mobile healthcare teams, improved transportation services, and policy reforms targeting priority issues. Stigma reduction and enhanced health literacy are crucial to managing chronic diseases and improving outcomes. A holistic approach, including poverty alleviation, educational initiatives, and gender-sensitive services, is essential to achieve sustainable health improvements.